A TYPE-2 FUZZY NETWORK DATA ENVELOPMENT ANALYSIS FOR FMCG DISTRIBUTORS’ PERFORMANCE EVALUATION WITH SUSTAINABILITY APPROACH - Olfat, Laya; Pishdar, Mahsa; Ghasemzadeh, Fatemeh (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
Because of the importance, sustainability of distribution centers in fast moving consuming goods (FMCG) sector is considered through a multi-perspective, multi-system and multi-process operation. It is explored how an extension of type-2 fuzzy network performance measurement approach helps to determine the efficiency performance of distribution centers in food and health products sector which are important products. A four-pronged approach is intended which considers management related elements, functions affecting the employees and retailers and also functions related to the environment simultaneously. This unprecedented combination makes it possible to have a comprehensive evaluation of distribution centers’ performance. Besides, type-2 fuzzy extension of SBM network approach causes it to better encounter with the vagueness of variables during analysis. Such extension is valuable from both technical and conceptual a aspect which in turn provides useful information and insights for the future design of holistic strategies connected with sustainability of FMCG supply chain as a whole.